Malaysia tourism demand model based on Singapore tourist / Mohammed Hakim Rafzanjani and Nor Fatiin Amirah Azmi - Rafzanjani, Mohammed Hakim; Azmi, Nor Fatiin Amirah (Faculty of Business and Management, 2013)
This paper investigates the short run and long run relationship Malaysia tourism demand. Data for the variables were obtained from World Development Indicators (WDI) from 1989 to 2012. The results based on the ARDL (1,1,2,1,2), the study documents a long run equilibrium between tourism demand, travelling cost, tourism price income and exchange rate. However the study discovers Malaysia tourism demand from Singapore tourist. A few policies implication can be recommended such as the government should provide more programs to encourage tourist to come to Malaysia. Another than that, government can do a collaboration with other countries such as Singapore to expand the tourism industry.